The administrative code of the “Estado Novo”: the juridical distribution of political power during the dictatorship - Codato, Adriano (2016)
This paper examines the two versions of the Decree 1.202/39 and its amendments during the Estado Novo dictatorship (Decrees 5.511/43 and 7.518/45). It analyzes the different formats of the legal provision that set the formal powers of the state oligarchies after the Revolution of 1930 and the political-bureaucratic agenda of the Administrative Departments of the states, evaluating their legal capacity to formulate policies and make decisions, as a precondition to understand their power of agenda-setting. This analysis explains how the division of political and bureaucratic work operated in the dictatorial state, the connections between its centers of power and the distribution of power among oligarchies.